DEVELOPING RETURN BOARD AS AN AID FOR FOREHAND TOPSPIN IN TABLE TENNIS - Santosa, Teguh; Setiono, Hari; Sulaiman, Sulaiman (The Journal of Educational Development, 2017)
This study is aimed at developing a return board aid, and assisting athletes and coaches to improve the ability in using forehand topspin in table tennis.  A Borg and Gallâs research and developmental method is used consisting the following steps: identification of potentials and problems, data collection, developing a preliminary product, expert judgement and revision, small-scale field testing and revision, large-scale field testing, large-scale revision, product application field testing, product revison, and mass production. Ten athletes were involved in the small scale field testing and forty-two athletels were involved in the large-scale field testing. Product validation was conducted by six experts, includingt 3 practitioners and 3 lecturers. The data were collected by using interviews, observation, and test of product effectiveness, and analysed by using a mini tab 16. The findings show that the return board as a medium aid can be used to improve the ability of the athletes in applying forehand topspin. The product was found to be 53% effective for beginners and 32% effective for advanced athletes. The return board product can be used as a means for practice for junior, beginner, and senior athletes. The product can also be used to motivate athletes in their practice by assessing their ability in forehand topspin stroke.